Apologetics in Africa: An Introduction #AfricanApologetics - Ndereba, Kevin Muriithi (2019)
In an age of religious tolerance and political correctness, Christians are pressured to apologise for what they believe in. Talk of God, faith, repentance, holiness, salvation and eternity in an age of many choices, is cushioned in politeness, hushed tones, diluted convictions and platitudinous confessions. Winsomeness has its place, but half-hearted witness is ineffective for our time. Social media timelines are filled with videos and images that are a reflection of how much we have elevated the self, to the point of obscuring any confrontation of ideas, except those ideas that are non-Christian. On the other hand, African Christianity is...
free